2020
DOI: 10.3390/d12030111
|View full text |Cite
|
Sign up to set email alerts
|

Do Invasive Mosquito and Bird Species Alter Avian Malaria Parasite Transmission?

Abstract: Alien mosquito and vertebrate host species may create novel epidemiological scenarios for the transmission of pathogens naturally circulating in the invaded area. The exotic Monk parakeet (Myiopsitta monachus) has established populations in Europe and is currently considered an invasive pest. Due to their high abundance in urban areas, Monk parakeets could be involved in the transmission of pathogens, potentially affecting wildlife and livestock. To test this hypothesis, we determined the prevalence and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…These results provide valuable information regarding the blood-feeding sources of these species, which is especially relevant in the case of Ae. albopictus as this subject has only to date been investigated at a handful of studies in Europe ( 6 , 25 , 28 , 33 ). Identification of the blood-meal sources of mosquitoes in zoos allows researchers to investigate additional aspects of vector ecology such as the flight distances of engorged females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results provide valuable information regarding the blood-feeding sources of these species, which is especially relevant in the case of Ae. albopictus as this subject has only to date been investigated at a handful of studies in Europe ( 6 , 25 , 28 , 33 ). Identification of the blood-meal sources of mosquitoes in zoos allows researchers to investigate additional aspects of vector ecology such as the flight distances of engorged females.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that encounters between infected birds and competent mosquito vectors frequently occur in the area, which probably facilitates the transmission of avian Plasmodium within this zoo ( 12 , 15 , 23 , 24 ). Previous studies in the Iberian Peninsula have identified avian Plasmodium in mosquitoes of the genera Culex and Aedes ( 25 , 32 , 35 , 36 ), and of them, Cx. pipiens probably plays a key role in the transmission of avian Plasmodium due to its wide distribution ( 1 ), competence for the transmission of different avian Plasmodium lineages/species ( 16 , 37 ), and its ornithophilic behavior ( 6 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, according to Medlock et al and Martínez-de la Puente et al [24,25], invasive mosquito species Asian tiger mosquito (Aedes albopictus), originated from SE Asia is spreading in some parts of Europe already. The presence of Plasmodium vaughani (genetic lineage pSYAT05) DNA was recorded in these mosquitoes collected in Italy [25] and according to Martínez-de la Puente et al [26], this mosquito could also be a potential vector for other avian malaria parasites, especially those originated from SE Asia.…”
Section: Page 3/25mentioning
confidence: 94%